Model Perencanaan Produksi untuk Memenuhi Permintaan Pasar dan Pengendalian Persediaan Produk Jadi pada Perusahaan Penghasil Minuman Ringan - Ni Made Darmayanti; I Wayan Widia; Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2016)
This research aims to determine the historical pattern of sales of each product variant, the index of special events that influence the demand and forecasting models are most appropriate to use as the basis for planning the production of Coca-Cola 200 ml and Sprite 295 ml in PT. CCBI Balinusa. From these studies obtained pattern on the monthly sales of each product in 2015 fluctuated from time to time. The highest sales of Coca-Cola 200 ml occurred in September, and Sprite 295 ml occurred in December. While the lowest sales data on Coca-Cola 200 ml and Sprite 295 ml occurred in July. Index top special event for Coca-Cola 200 ml is on Christmas and New Year (I=2.43), the lowest was Idul Adha (I=1.42) and Sprite 295 ml highest at Christmas and New Year (I=2.17), the lowest in the Waisak (I=1.47). The best forecasting model for Coca-Cola 200 ml is an exponential smoothing event based (ESEB) with α = 0.3 and for Sprite 295 ml is an exponential smoothing event based with α = 0.1.